2009
DOI: 10.1002/eji.200939754
|View full text |Cite|
|
Sign up to set email alerts
|

Modified vaccinia Ankara‐expressing Ag85A, a novel tuberculosis vaccine, is safe in adolescents and children, and induces polyfunctional CD4+ T cells

Abstract: Summary MVA85A is a new tuberculosis vaccine aimed at enhancing immunity induced by BCG. We investigated the safety and immunogenicity of MVA85A in healthy adolescents and children from a tuberculosis endemic region, who received BCG at birth. Twelve adolescents and 24 children were vaccinated and followed up for 12 or 6 months, respectively. Adverse events were documented and vaccine-induced immune responses assessed by IFN-γ ELISpot and intracellular cytokine staining. The vaccine was well tolerated and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 48 publications
13
160
6
1
Order By: Relevance
“…In this context, it is noteworthy that other studies also have reported reactivity to MTB-encoded antigens in HCs and NTM-infected/exposed individuals that is hypothesized to be as a result of exposure to NTMs (7,8,31). Furthermore, NTM exposure may explain the higher baseline reactivity to PPD that was found in MTB-naive young adults as compared with children (32). Other studies highlighted that the majority of small MTB-PPD reactions could be attributed to NTM exposure or disease (33).…”
Section: Discussionmentioning
confidence: 87%
“…In this context, it is noteworthy that other studies also have reported reactivity to MTB-encoded antigens in HCs and NTM-infected/exposed individuals that is hypothesized to be as a result of exposure to NTMs (7,8,31). Furthermore, NTM exposure may explain the higher baseline reactivity to PPD that was found in MTB-naive young adults as compared with children (32). Other studies highlighted that the majority of small MTB-PPD reactions could be attributed to NTM exposure or disease (33).…”
Section: Discussionmentioning
confidence: 87%
“…In humans, vaccination with a novel tuberculosis vaccine based on modified Vaccinia virus Ankara expressing Ag85A (MVA85A) induces T cells with complex phenotypic and polyfunctional cytokine-secreting profiles, including a less differentiated group that co-expresses IFN-g, TNF and IL-2, and with the ability to proliferate. Such cells are considered more likely than single cytokine secretors to be associated with protection [10,11]. Another novel TB vaccine, based on a recombinant replicationdeficient adenovirus (Ad35)-expressing TB antigens, also induces a robust polyfunctional CD4 1 T-cell response in adults [12].…”
mentioning
confidence: 99%
“…Interestingly, in The Gambian study, the immunogenicity of MVA85A in BCG vaccinated (BCG+) and BCG naive (BCG-) adults was comparable, in contrast to studies in the UK where immunogenicity was higher in BCG vaccinated subjects [6]. Furthermore in South Africa, the immunogenicity of MVA85A in BCG vaccinated adults was also comparable to that seen in BCG naïve adults [8]. These findings suggest that MVA85A may boost cumulative mycobacterial exposure which is comprised of exposure to BCG, non-tuberculous mycobacteria and M.tb, and that the contribution of BCG to this cumulative mycobacterial exposure is less relevant in adults in TB endemic countries.…”
Section: Introductionmentioning
confidence: 72%
“…MVA85A was safe well tolerated and immunogenic when administered to adult volunteers in the UK, The Gambia and South Africa [6][7][8]. Interestingly, in The Gambian study, the immunogenicity of MVA85A in BCG vaccinated (BCG+) and BCG naive (BCG-) adults was comparable, in contrast to studies in the UK where immunogenicity was higher in BCG vaccinated subjects [6].…”
Section: Introductionmentioning
confidence: 86%